Association between the Alpha-1-acid glycoprotein concentrations and depression in US adult women: a cross-sectional study from NHANES 2021–2023 - Zhao, Wanchen; Zhang, Hui; Li, Zhen; Ma, Cong; Huo, Xiaopeng; Guo, Na (Frontiers in Psychiatry, 2025)
BackgroundRecent evidence suggests that there is a close correlation of inflammation with depression. Therefore, our study aims to explore the association of Alpha-1-acid glycoprotein (AGP), a highly sensitive inflammatory biomarker, with depression in US adult women.MethodsData from the National Health and Nutrition Examination Survey (NHANES) from 2021-2023 were selected for this study. Both AGP concentrations and depression levels were assessed using standardized survey instruments. Multivariate logistic and linear regression, and restricted cubic splines models (RCS) were performed to evaluate the relationship of AGP concentrations with depression. Stratified analyses and multiplicative interaction testing were conducted to evaluate the robustness of the observed association across relevant subgroups.ResultsAGP concentrations demonstrated a positive linear association with depression among US adult women. Each standardized unit increment in ln-transformed AGP concentrations was associated with significantly higher odds of depression (OR = 2.04, 95% CI: 1.17-3.57) and a 1.47-point increase in PHQ-9 scores (β = 1.47, 95% CI: 0.37-2.56) in the fully adjusted model. Furthermore, compared with participants in the lowest AGP concentration quartile, those in the highest quartile exhibited 72% greater odds of depression (OR = 1.72, 95%CI: 1.03-2.87), and 1.32-point higher PHQ-9 scores (β = 1.32, 95%CI: 0.31-2.34) in the fully adjusted model. This positive association remained consistent across several subgroups and our sensitivity analysis. In addition, compared to C-reactive protein (CRP), AGP had a stronger predictive effect on depression using the ROC curve.ConclusionsAGP exhibited a positive linear association with depression in US adult women. This positive association remained consistent across several subgroups. Furthermore, AGP had a stronger predictive effect on depression compared to CRP.